Fat-Soluble Nutrients and Omega-3 Fatty Acids as Modifiable Factors Influencing Preterm Birth Risk - Thoene, Melissa (Placenta, 2019)
Preterm birth is a leading cause of child morbidity and mortality, so strategies to reduce early birth must remain a priority. One key approach to enhancing birth outcomes is improving maternal dietary intake. Therefore, the purpose of this review is to discuss mechanisms on perinatal status of fat-soluble nutrients (carotenoids, retinol, tocopherols) and omega-3 fatty acids and how they impact risk for preterm birth. Literature review demonstrates that maternal dietary intake and biological (blood and placental tissue) levels of fat-soluble nutrients during pregnancy may provide antioxidative, anti-inflammatory, and immunomodulatory health benefits. Omega-3 fatty acids also promote increased production of specialized pro-resolving mediators, subsequently mediating inflammation resolution. Combined effects of these nutrients support appropriate placental organogenesis and function. Consequently, fat-soluble nutrients and omega-3 fatty acids serve as strong influencers for preterm birth risk. As dietary intake remains a modifiable factor, future intervention would benefit from a focus on optimizing perinatal status of these specific nutrients.